Popular Sovereign Generated Versus Government Institution Generated Constitutional Norms: When Does a Constitutional Amendment Not Amend the Constitution? - Carlos E. González (Washington University Law Quarterly, 2002)
An elementary principle of constitutional law is that a constitutional amendment nullifies, or at least alters, preexisting and conflicting constitutional provisions. Yet should all constitutional amendments have this effect? Can we imagine a scenario in which ratification of a new constitutional amendment would leave preexisting conflicting constitutional provisions fully intact, unaltered, and undisturbed? This Article argues that the best understanding of fundamental adjudicatory principles compels us to recognize just such a possibility.
Keywords: Popular sovereignty; Constitutional amendments; Constitutional law; Constitutional interpretation